2019
DOI: 10.7181/acfs.2019.00549
|View full text |Cite
|
Sign up to set email alerts
|

Intramasseteric schwannoma treated with facelift incision and retrograde facial nerve dissection

Abstract: Schwannoma is a slow-growing, well-demarcated, benign soft tissue tumor of the peripheral nerve sheath. It commonly develops in the head and neck region, usually in the parapharyngeal space. In this case, a 42-year-old woman visited the outpatient department to manage a painless mass on her left cheek. She had no history of concern and no neurological symptoms were observed. In the enhanced computed tomography scan, a 2.8 × 2.8 × 1.8 cm, heterogeneously enhanced tumor was detected in the left masseter muscle. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…A review of the English-language literature reveals only 10 reported cases of schwannomas located at the intramasseteric region (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). As shown in Table 1, a female-to-male ratio of 1:1 was observed and there is no signi cant gender predilection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A review of the English-language literature reveals only 10 reported cases of schwannomas located at the intramasseteric region (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). As shown in Table 1, a female-to-male ratio of 1:1 was observed and there is no signi cant gender predilection.…”
Section: Discussionmentioning
confidence: 99%
“…As evident in Table 1, FNA biopsies were performed in 4 cases and all inconclusive, indicating that FNA has a low accuracy in the diagnosis of schwannoma. Therefore, the conclusive diagnosis is only achieved based on microscopic ndings of the harvested tissues, characterizing with a speci c cellular Antoni A areas and less organized hypocellular Antoni B areas [16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In these cases, a schwannoma can be removed by including only part of the fascicles or by cutting the capsule. However, if there is significant fascicular involvement, neurorrhaphy or a nerve graft may inevitably be required to minimize neurologic deficit after en bloc excision [ 10 , 11 ]. Although schwannomas are benign, incomplete excision can cause a slow local recurrence over months to years [ 9 ].…”
Section: Discussionmentioning
confidence: 99%